Penerapan Sistem Inventory Berbasis Open Source Odoo pada Optik Family - Wijaya, Pierediaz Putra; Riyadi, Arohmah; Hajar, Dewi (MEDIANTARA: Indonesian Journal of Creative Business and Technology (IJCBT), 2025)
The continuous advancement of technology requires every business sector to constantly adapt. One of the most widely used technologies in the business sector is Enterprise Resource Planning (ERP) software, which integrates all core business processes. ERP software comes in various forms, each with its own strengths and unique features. For this study, we selected Odoo ERP as the solution platform to address the challenges faced by Micro, Small, and Medium Enterprises (MSMEs). Odoo ERP was chosen because it is considered more user friendly and accessible for various types of businesses, including MSMEs. This research aims to implement the Odoo ERP system for the MSME Optik Family , which has been experiencing issues with inventory recording that often results in inaccuracies and disrupt several business processes. The study begins by designing Porter’s Value Chain Model to identify the potential application of Odoo ERP modules in the company’s primary activities. The developed system is then tested using the Black Box Testing method to assess the functionality of each module. The designed Odoo ERP system includes modules for product ordering, inventory storage, and invoicing. These three modules enable realtime inventory monitoring and provide accurate historical data. Testing results confirm that the implemented modules function properly and significantly accelerate the previously manual inventory recording processes. The improved speed and accuracy in stock data recording contribute to faster, more efficient, and more precise operational activities for the optical business.